Pembuatan Sistem Pencatatan Pinjaman Kelompok Wanita Tani Berbasis Web Menggunakan Metode V-Model - Kusnadi; Amroni; Fauzan Rahmawan Maryus (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research focuses on designing a web-based loan recording system for the Jati Mekar Women Farmers Group (KWT) in Sindanglaut Village. KWT Jati Mekar is an organization consisting of women farmers in Sindanglaut Village who have joined together to improve their welfare and productivity through various agricultural and economic activities.The main objective of the research is to develop a system that can increase efficiency and accuracy in recording group members' loans. The methodology used is the V-Model, which allows for structured and systematic system development through stages of requirements analysis, design, implementation, testing, and maintenance.This system is designed to facilitate the process of recording, monitoring, and reporting loans, as well as increasing transparency in the group's financial management. During the development process, blackbox testing was conducted to evaluate the system's functionality without examining the internal code structure. This testing focuses on the system's inputs and outputs, ensuring that each feature functions according to expected specifications.The research results show that the implementation of this web-based system can address problems that often occur in manual recording, such as inaccurate data and difficulties in tracking loan status. Blackbox testing verifies that the system can handle various usage scenarios correctly, including member data management, loan recording, and report generation.